Pupil Dilation and Microsaccades Provide Complementary Insights into the Dynamics of Arousal and Instantaneous Attention during Effortful Listening - Contadini-Wright, Claudia; Magami, Kaho; Mehta, Nishchay; Chait, Maria (The Journal of neuroscience, 2023)
Listening in noisy environments requires effort- the active engagement of attention and other cognitive abilities- as well as increased arousal. The ability to separately quantify the contribution of these components is key to understanding the dynamics of effort and how it may change across listening situations and in certain populations. We concurrently measured two types of ocular data in young participants (both sexes): pupil dilation (PD; thought to index arousal aspects of effort) and microsaccades (MS; hypothesized to reflect automatic visual exploratory sampling), while they performed a speech-in-noise task under high- (HL) and low- (LL) listening load conditions. Sentences were manipulated so that the behaviorally relevant information (keywords) appeared at the end (Experiment 1) or beginning (Experiment 2) of the sentence, resulting in different temporal demands on focused attention. In line with previous reports, PD effects were associated with increased dilation under load. We observed a sustained difference between HL and LL conditions, consistent with increased phasic and tonic arousal. Importantly we show that MS rate was also modulated by listening load. This was manifested as a reduced MS rate in HL relative to LL. Critically, in contrast to the sustained difference seen for PD, MS effects were localized in time, specifically during periods when demands on auditory attention were greatest. These results demonstrate that auditory selective attention interfaces with the mechanisms controlling MS generation, establishing MS as an informative measure, complementary to PD, with which to quantify the temporal dynamics of auditory attentional processing under effortful listening conditions. Listening effort, reflecting the "cognitive bandwidth" deployed to effectively process sound in adverse environments, contributes critically to listening success. Understanding listening effort and the processes involved in its allocation is a major challenge in auditory neuroscience. Here, we demonstrate that microsaccade rate can be used to index a specific subcomponent of listening effort, the allocation of instantaneous auditory attention, that is distinct from the modulation of arousal indexed by pupil dilation (currently the dominant measure of listening effort). These results reveal the push-pull process through which auditory attention interfaces with the (visual) attention network that controls microsaccades, establishing microsaccades as a powerful tool for measuring auditory attention and its deficits.